Features of speech formation in preschool children - Bakhtiyor kizi, Bakirova Umida (PT. Antis International Publisher, 2024)
Speech - a wonderful gift of nature - is not given to a person from birth. It takes time for the child to start talking. And adults should make a lot of efforts so that the speech of the child develops correctly and in a timely manner.